TRANSFORMATION OF THE GENDER DICHOTOMY OF SPIRIT AND BODY IN POSTMODERN PHILOSOPHY AND CULTURE - O. P. Vlasova; Y. V. Makieshyna (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The signification of the theoretical grounds for the conceptual reconstruction of the dichotomy "spirit-body" in the field of postmodern notions in philosophy and culture, the identification of the location of the given dichotomy in the processes of the transition of philosophy from being classical to the postclassical one, simultaneously, culture – to the cultural forms of postmodernity. Theoretical basis. The changing systems of post paradigm relations, radically transforming human life in the postmodern world, represent the obvious transformations of the fundamental conceptual schemes. For postmodern philosophers, the dichotomy "spirit-body" does not mean better interpretation of separate substances any more, but the development of the relationship between mental and physical properties. Feminist philosophers assert that the "spirit-body" opposition occupies the special place among classical dichotomies, as it acquires the key meaning in the patriarchal concepts of masculinity and femininity. In the post modernity, the body and corporality become dominant themes not only in the philosophy and "high" culture, but also in mass culture; at the same time, the emphasis on their common narratives and intertexts testifies to the fundamental transformations that reflect the "condition" of postmodernity. Originality of this research lies in the expose of the specific transformation features of the dichotomy "spirit-body" as a philosophic opposition closely connected with postmodernism and realized in the practices of mass culture. This research is reflectedof the idea of the absoluteness and invariabilityof this duality as thebasicdichotomy of the classical philosophy in its correlation with cultural logic of the postmodernity at the end of the 20 – the beginning of the 21st centuries. Conclusions. With the reinterpretation of the "spirit-body" dichotomy, the body is theorized as a cognitive agent with desires independent of the mind. In postmodernism, the body is the source of charm, and aversion and destruction, and restoration. At the same time, with the growth of the visualization factor and the change in the status of "high" culture, the "turn" in the status of mass culture is created: today both the former and the letter have many common discourses, narratives and intertexts.